PROBING PROMPTING TECHNIQUE ASSISTED BLENDED LEARNING VIEWED FROM TRIALS AND KAM ON THE ABILITY OF PROBLEMS AND UNDERSTANDING MATHEMATIC STUDENTS IN UNIVERSITY PGRI PALEMBANG - Jayanti, Jayanti; Rahmawati, Rahmawati (Sriwijaya University Learning and Education International Conference, 2018)
This study aims to examine the extent of test results and initial ability of students (KAM) on the ability of Mathematical Problem Solving (KPMM) and mathematical understanding (KPM) of students through Probing Prompting learning techniques. Probing methods developed with Prompting are as follows: The teacher exposes the student to a new situation, for example by looking at pictures, formulas or other situations that contain problems. Waiting for a moment to give the students an opportunity to formulate an answer or conduct a small discussion in formulating it, The teacher asks students to match the specific learning objectives (TPK) or indicators to all students, waiting for a moment to give the students an opportunity to formulate an answer or conduct a small discussion in formulating it. In the face-to-face study dikuliah Differential Equation, assisted blended learning is by using the internet online. This research uses test class and also see KAM that is student ability early on high level, medium and low. The subject of this research is a mathematics student at PGRI University of Palembang. Based on the results of the analysis seen the results of tests on indicators of problem-solving skills and students' mathematical understanding, as well as the initial ability (KAM).